Fincancilar Yokusu, Amerikan Hani, and Printing Activities in Istanbul in the Nineteenth and Twentieth Centuries - Turna, Nalan (ANKARA UNIV, FAC COMMUNICATION, 2020)
This article will examine nineteenth- and twentieth-century Ottoman printers and their printing activities in the specific context of the Fincancilar Yokusu, which is now located in Istanbuls Fatih district. In the same context, it will consider the Amerikan Hani, or Bible House, built there in the nineteenth century by American Protestant missionaries. The article will show that the printing profession in the area was dominated by American missionaries, Ottoman Armenians (especially Protestant Armenians), and Ottoman Muslims. Through examples of what was published in the Fincancilar Yokusu, it will shine a light on the reading habits of the period and possible new imaginations of Ottoman Protestant Armenians. Finally, it will offer some conclusions about the areas in which the printers at this particular location were dependent on Europe and how, in certain cases, they overcame this dependency. In short, the aim of this article is to examine the printing activities in the Fincancilar Yokusu, and thus to capture some of the realities of the reading habits and intra-imperial and trans-imperial relation networks of American missionaries and Ottoman Protestant Armenians in the nineteenth- and twentieth-century Ottoman Empire.
Keywords: Istanbul Fincancilar Yokuu; printing activities; Amerikan Hani/Bible House; Protestant missionaries; Protestant Armenians; Communication